Pengaruh Belanja Daerah Dan Kemahalan Konstruksi Terhadap Pembangunan Manusia Dengan Opini Badan Pemeriksa Keuangan Sebagai Variabel Moderasi Di Provinsi Papua - Paul; Salle, Agustinus; Purba Riani, Ida Ayu (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2024)
This study aims to empirically examine the effect of regional spending and construction costs on HDI with BPK audit opinion as a moderating variable.This study uses a panel data structure from 29districts/cities in Papua Province for nine years (2011-2019). The model used is fixed effect throughHausman test. The results of statistical tests show that the regional expenditure variable has a positive and significant effect on the HDI, while the level of construction costs has a negative and significant effect on the HDI. The statistical test results also show that the audit opinion weakens the influence of regional https://www.adenomyosisadviceassociation.org/hysterectomy spending on HDI, and strengthens the effect of construction costs on HDI. Keywords: regional expenditure, human development index (hdi), construction cost index (cci), andaudit opinion